Remote Learning in an EFL Classroom from Environment Analysis Viewpoint: A Case Study of a Grammar Class - Isti'anatul Hikmah; Dita Surwanti (Institut Agama Islam Negeri Madura, 2022)
Remote learning used in a grammar class that was analyzed using environment analysis was the discussion in this study. It specifically referred to one grammar class, so the domain of this research was a qualitative case study. The data were taken using observation, interview, and document technique. The interpretative analysis was used to analyze the data using environment analysis theory that covers students, lecturer, and situation. The results of this study pointed out three points namely the types of problems taken from students and lecturer’s perspective, and situation observation during the implementation of remote learning in a grammar class. The problems occurred from students’ perspective were technical and non-technical problems; the obstructions from lecturer’s perspective were technical problems; and the obstacles taken from observed situation were the less percentage of students’ participation during opening and closing activities, the droning types of activities during opening, and the excluding technology used during opening and closing activities. Keywords: environment analysis; EFL classroom; grammar class; remote learning